2007
DOI: 10.1111/j.1536-7150.2007.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

What Do Bettors Want? Determinants of Pari‐Mutuel Betting Preference

Abstract: This paper is an analysis of the demand for thoroughbred racetrack wagers, examining evidence that would support the existence of two types of bettors: the risk-averse informed bettor versus the uninformed bettor. Looking at 12 major racetracks over the fall of 2002, we undertake an empirical examination of the determinants of bettors' preferences for particular wagers on specific races. The goal is to try to determine what individual aspects of a race (conditions, surface, participants, etc.) will encourage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…This has hardly been done in the past. Gramm, McKinney, Owens, and Ryan (2007) investigate what drives betting volumes in horse racing. They find that the day of the event is important as the quality of the participants raises betting volume, while a larger number of simultaneous races has a negative effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has hardly been done in the past. Gramm, McKinney, Owens, and Ryan (2007) investigate what drives betting volumes in horse racing. They find that the day of the event is important as the quality of the participants raises betting volume, while a larger number of simultaneous races has a negative effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lottery and other forms of gambling, including Indian casinos and sports betting, are viewed as competing gambling products that may adversely impact horse wagering. The empirical evidence, however, is somewhat mixed; Gramm et al . (2007) find that the lottery does not have a statistically significant impact on horse wagering.…”
Section: Data and Backgroundmentioning
confidence: 99%
“…Large purses attract higher quality horses, resulting in bigger wager pools. Gramm et al . (2007) assert that higher purse per race is a good proxy for “race quality.”…”
Section: Data and Backgroundmentioning
confidence: 99%
“…6 New York, for example, mandates minimum takeout rates of 15% for win/place/show bets, though it appears that only Tioga Downs since its recent reduction is presently at those minima. 7 Churchill Downs 2009 annual report, p. 48. 8 The Interstate Horseracing Act of 1978 (Public Law 95-515) stipulates that off-track betting facilities are subject to the same regulations regarding takeout as the racetracks themselves and that such facilities Fixed odds gambling in horse racing (as can be found in Australia, Ireland, the United Kingdom, and several other countries) differs from pari-mutuel wagering in several ways.…”
Section: Institutions: American and Australianmentioning
confidence: 99%
“…Previous researchers have used variation in takeout rates and amounts wagered to estimate price-elasticities for U.S. pari-mutuel gambling (Gruen, 1976;Suits, 1979;Mobilia, 1993;Thalheimer and Ali, 1998;Gramm et al, 2007). These studies have generally found 1 Laurel Park halved its takeouts across the board for ten days in August 2007.…”
mentioning
confidence: 99%